Research Mapping on Personal Data Protection Policy - Unas, Frisca Maria; Yuadi, Imam (Department of Government Studies, Universitas Syiah Kuala, 2023)
The need for Personal Data Protection must be supported by policies that are able to guarantee the security of personal information so that it is not misused by irresponsible persons. The development of research on personal data protection policy can be a good reference for the government and stakeholders in formulating policies that can guarantee the security of personal data. This study aims to determine research trends and explain the relationship between keywords and researchers in research articles on personal data protection policies. This study uses the bibliometric analysis method assisted by the VOS Viewer and Biblioshiny Rstudio tools so that it can display interesting network visualization. The findings from this study are the development of research publications on related topics from year to year, mapping of subject areas of research publications on related topics, mapping of countries of origin of research publications on related topics, relationships between authors/researchers, relationships between keywords from a number of research articles on related topics, distribution of journals that publish research articles on related topics, and productivity of researchers/writers of articles on related topics. The results of this study can help researchers find novelty opportunities and use appropriate reference sources in conducting research on related topics